Deciphering the toxic effects of polystyrene nanoparticles on erythropoiesis at single-cell resolution - Kwon, Eun Jung; Sung, Hyeon Mi; Lee, Hansong; Ahn, Soyul; Kim, Yejin; Lee, Chae Rin; Kim, Kihun; Myung, Kyungjae; Kim, Won Kyu; Kim, Dokyoung; Jeong, Sanghwa; Oh, Chang-Kyu; et al. (Science Press, 2025)
Polystyrene nanoparticles pose significant toxicological risks to aquatic ecosystems, yet their impact on zebrafish ( Danio rerio) embryonic development, particularly erythropoiesis, remains underexplored. This study used single-cell RNA sequencing to comprehensively evaluate the effects of polystyrene nanoparticle exposure on erythropoiesis in zebrafish embryos. In vivo validation experiments corroborated the transcriptomic findings, revealing that polystyrene nanoparticle exposure disrupted This is an open-access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http:// creativecommons.org/licenses/by-nc/4.0/), which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. erythrocyte differentiation, as evidenced by the decrease in mature erythrocytes and concomitant increase in immature erythrocytes. Additionally, impaired heme synthesis further contributed to the diminished erythrocyte population. These findings underscore the toxic effects of polystyrene nanoparticles on hematopoietic processes, highlighting their potential to compromise organismal health in aquatic environments.